Eco Consciousness and Consumer Perception: An Explanatory Study of Environmentally Friendly Product Purchasing Decisions in Makassar City - Hasnidar Hasnidar; Achmad Ridha (PT. Maju Malaqbi Makkarana, 2026)
This study aims to describe and explain consumer perceptions of environmentally friendly products and their impact on purchasing decisions in Makassar City. With increasing attention to environmental issues and changes in urban lifestyles, it is important for businesses to understand how consumers assess sustainability oriented products. This study uses a qualitative explanatory approach with data collection techniques through in depth interviews, observation, and documentation. Twelve research informants were selected through purposive sampling, consisting of 12 active consumers of environmentally friendly products domiciled in Makassar City, conducted over a three month period from January to March 2026. The results show that consumer perceptions of environmentally friendly products are influenced by three main dimensions, namely: (1) environmental awareness (eco consciousness), (2) trust in green claims, and (3) perception of multidimensional product value. These three dimensions together form a positive attitude that ultimately drives purchasing decisions for environmentally friendly products. In line with the findings of (Hasnidar & Ridha, 2025) which confirmed that eco consciousness and perception of sustainable packaging have a significant influence on green purchasing behavior through the mediation of consumer attitudes, this study enriches this understanding with a qualitative perspective that explores consumers' subjective meanings and experiences in depth.